HYGIENIC CHARACTERISTICS OF THE SOCIAL PORTRAIT, CONDITIONS AND LIFESTYLE OF INFECTIOUS DISEASES DOCTORS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article presents the results of a medical and sociological study. The hygienic characteristics of the social portrait, conditions and lifestyle of infectious diseases doctors are revealed and their analysis is carried out. Infectious disease doctors rated their family's well-being as average or below average.